Anatomic predictors of response and mechanism of action of upper airway stimulation therapy in patients with obstructive sleep apnea. Issue 4 (26th March 2018) - Schwab, Richard J; Wang, Stephen H; Verbraecken, Johan; Vanderveken, Olivier M; Van de Heyning, Paul; Vos, Wim G; DeBacker, Jan W; Keenan, Brendan T; Ni, Quan; DeBacker, Wilfried
Abstract: Study Objectives: Upper airway stimulation has been shown to be an effective treatment for some patients with obstructive sleep apnea. However, the mechanism by which hypoglossal nerve stimulation increases upper airway caliber is not clear. Therefore, the objective of this study was to identify the mechanism of action of upper airway stimulation. We hypothesized that, with upper airway stimulation, responders would show greater airway opening in the retroglossal (base of the tongue) region, greater hyoid movement toward the mandible, and greater anterior motion in the posterior, inferior region of the tongue compared with nonresponders. Methods: Seven participants with obstructive sleep apnea who had been successfully treated with upper airway stimulation (responders) and six participants who were not successfully treated (nonresponders) underwent computed tomography imaging during wakefulness with and without hypoglossal nerve stimulation. Responders reduced their apnea–hypopnea index (AHI) by 22.63 ± 6.54 events per hour, whereas nonresponders had no change in their AHI (0.17 ± 14.04 events per hour). We examined differences in upper airway caliber, the volume of the upper airway soft tissue structures, craniofacial relationships, and centroid tongue and soft palate movement between responders and nonresponders with and without hypoglossal nerve stimulation. Results: Our data indicate that compared with nonresponders, responders had a smaller baseline soft palate volume and, with stimulation, had (1) a greater increase in retroglossal airway size; (2) increased shortening of the mandible-hyoid distance; and (3) greater anterior displacement of the tongue. Conclusions: These results suggest that smaller soft palate volumes at baseline and greater tongue movement anteriorly with stimulation improve the response to upper airway stimulation.